DETOXIFICATION ENZYMES ACTIVITIES IN DDT AND BENDIOCARB RESISTANT AND SUCEPTIBLE MALARIAL VECTOR (Anopheles gambae) BREED IN AUYO RESIDENTIAL AND IRRIGATION SITES NORTHWEST NIGERIA - A. J., Alhassan; M. S., Sule; M.A., Dangambo; A. M., Yayo; M., Safiyanu; D., Sulaiman (European Scientific Journal, ESJ, 2015)
Evaluating levels of detoxifying enzymes is informative to governmental, nongovernmental organization and insecticides producing industries. In this work DDT and bendiocarb resistance status of Anopheles gambae breeds in Auyo (May – September, 2014) was studied. Larvae collected from residential sites (AR) and rice Irrigation sites (AI) of Auyo town in Auyo LGA Jigawa State Nigeria reared to adult was studied by WHO adult bioassay. Standard methods were adapted to determine the specific activities of insecticides detoxifying enzymes; glutathione s transferase (GST), esterase and monooxygenase in the insecticides resistant (r) and susceptible (s) vectors. In addition those tested with bendiocarb were analyzed for acetylcholinesterase activities. The finding of the study established high resistance status of the malarial vectors to DDT in both sites, low resistance status to bendiocarb in residential site and possible resistance to bendiocarb in irrigation site according to WHO interpretation. Significant (P<0.05) elevation in the activity of esterase and GST were seen in DDT resistant strain of residential site compared to susceptible (s). Significantly higher (P<0.05) specific activity of monooxygenase and acetyl cholinesterase was observed in bendiocarb resistant strain of both residential and irrigation sites, except for acetyl cholinesterase of irrigation site. Elevated activity of was observed in bendiocarb resistant strain of residential site. The finding of the study could be associated with indiscriminate use of insecticides in residential site against malarial vector and other flying insect and agrochemicals in the irrigation site. Base on this finding it may be concluded that conferring resistance to malarial vector is not restricted to agricultural area alone. Therefore challenge to researchers and chemical industries in fight against malarial should be redirected to producing specific irreversible and/or reversible inhibitors to these insecticides detoxifying enzymes.